2012
DOI: 10.7869/tg.2012.28
|View full text |Cite
|
Sign up to set email alerts
|

Celiac disease in the Red Sea state of Sudan

Abstract: Background and aim: Celiac disease is characterized by sensitivity to gluten that results in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…A Sudanese study where 172 patients with suspected CD were investigated, 128/172 (74%) had confirmed CD and 105/128 (82%) were aged ≤20 years [10]. 64/105 had gastrointestinal symptoms and the remainder (n = 41) had extraintestinal manifestations, such as stunted growth, bone or joint pain, anaemia, skin manifestations and peripheral neuropathy [10].…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations
“…A Sudanese study where 172 patients with suspected CD were investigated, 128/172 (74%) had confirmed CD and 105/128 (82%) were aged ≤20 years [10]. 64/105 had gastrointestinal symptoms and the remainder (n = 41) had extraintestinal manifestations, such as stunted growth, bone or joint pain, anaemia, skin manifestations and peripheral neuropathy [10].…”
Section: Epidemiologymentioning
confidence: 99%
“…A Sudanese study where 172 patients with suspected CD were investigated, 128/172 (74%) had confirmed CD and 105/128 (82%) were aged ≤20 years [10]. 64/105 had gastrointestinal symptoms and the remainder (n = 41) had extraintestinal manifestations, such as stunted growth, bone or joint pain, anaemia, skin manifestations and peripheral neuropathy [10]. Another Sudanese study where 38/60 (63%) were aged ≤20 years, revealed the most common symptoms as chronic diarrhoea, followed by iron deficiency anaemia, weight loss, abdominal pain, and delayed growth and puberty [11].…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…1 They did not discuss the recent publications about coeliac disease in sub-Saharan East Africa, especially in Sudan and Djibouti. 2,3,4 Coeliac disease does exist in inter-tropical Africa, even if HLA DQ2 and DQ8 haplotypes do seem less frequent and coeliac disease seroprevalence is lower in general population. 1,5 We recently published 17 cases of patients with coeliac disease seen in Djibouti between 2005 and 2007.…”
mentioning
confidence: 99%